Inklusion og udsathed - og deres bidrag til et nuancerende professionssprog - Molbæk, Mette; Villumsen, Anne Marie (Tidsskrift for Professionsstudier, 2019)
In this article we analyse and discuss how research on inclusion and children at risk can contribute to a more varied and nuanced language on well-being of children. We investigate central concepts relating to inclusion and children at risk and their implications for the language of the professions, i.e. the way the professionals understand and work with children’s well-being. We argue that both fields can benefit from each other’s language and primary focus thus it together with children and families becomes possible to meet in joined effort towards children’s well-being in and across day-care, school and home.